KONTEKSTUALISASI MENJAGA KETURUNAN DALAM PERNIKAHAN TERHADAP FENOMENA CHILDFREE - Ai Samrotul Fauziah (USRAH: Jurnal Hukum Keluarga Islam, 2026)
This study analyzes the childfree phenomenon in relation to the Islamic concept of preserving lineage (ḥifẓ al-nasl) as one of the main purposes of marriage. The research employs a qualitative method with a library research approach and descriptive–narrative analysis. Data were obtained from scholarly literature, accredited journals, and relevant Islamic legal documents. The findings indicate that the decision to be childfree is influenced by economic, social, cultural, and psychological factors that often contradict religious teachings and social norms in Indonesian society. From an Islamic perspective, preserving lineage is part of the maqāṣid al-sharī‘ah, which emphasizes the continuity of the ummah and demographic balance. This study recommends strengthening social policies, Islamic-based family education, and psychological support for productive-age couples to enhance their readiness for parenthood and maintain generational sustainability in the future.